Literature Review: Building an Entrepreneurial Spirit - Edi Irawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to review and attempt to inform about the concept of building an entrepreneurial spirit. The research methods used are qualitative and literature study or library research. Based on the results of the discussion, it can be concluded that building an entrepreneurial spirit for beginners requires a mature strategy, one of which is the Contextual Teaching and Learning (CTL) approach. The contextual approach (CTL) is a learning concept that assumes that children will learn better if the environment is created naturally, meaning that learning will be more meaningful if children